Physicochemical Variation of Clay Minerals and Enrichment of Rare Earth Elements in Regolith-hosted Deposits: Exemplification from The Bankeng Deposit in South China - Li, Martin Yan Hei; Zhou, Mei-Fu (Clays and clay minerals, 2023)
The wide application of rare earth elements (REEs) in the development of a carbon–neutral society has urged resource exploration worldwide in recent years. Regolith-hosted REE deposits are a major source of global REE supply and are hosted mostly in clay minerals. Nonetheless, the ways in which changes in the physicochemical properties of clay minerals during weathering affect the concentrations of REEs in the regolith are not well known. In the current study, a world-class regolith-hosted REE deposit (Bankeng, South China) has been studied to illustrate further the effect of clay minerals on sorption and fractionation of REEs during weathering to form economic deposits. In the weathering profile, halloysite and illite are abundant in the saprolite due to weathering of feldspars and biotite from the bedrock. During weathering, halloysite and illite transform gradually to kaolinite and vermiculite. The large specific surface area, pore volume, and cation exchange capacity of the clay mineral assemblages are favorable to the sorption of REEs, probably because of the formation of vermiculite. The abundance of vermiculite could explain the enrichment of REEs in the upper part of the lower pedolith. For the saprolite-pedolith interface, halloysite is probably the main sorbent for the REEs, as indicated by the distinctive appearance of pore sizes of 2.4–2.8 nm characteristic of halloysite. The progressive transformation of halloysite to kaolinite reduces the pores and desorbs the REEs, causing REE depletion in the shallower soils. As a result, REEs were mobilized downward and re-sorbed in the lower pedolith-upper saprolite causing gradual enrichment and formation of these regolith-hosted deposits.